2019
DOI: 10.1016/j.btre.2019.e00322
|View full text |Cite
|
Sign up to set email alerts
|

Cooking with EDTA reduces nutritional value of Vicia faba beans

Abstract: HighlightsChefs used EDTA to accelerate the cooking time of Vicia faba beans.By ESI-MS analysis, disodium EDTA disappeared after cooking process of beans.Up on EDTA addition during cooking, essential nutrients changed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…To accelerate the cooking process and reduce the cost of cooking, some chefs use additives such as citric acid, sodium bicarbonate, and ethylenediaminetetraacetic acid (EDTA) (Lamas et al, 2014; Lanigan and Yamarik, 2002) where the latter was found to decrease the degree of starch gelatinization of black beans ( Phaseolus vulgaris L. ) (Mubaiwa et al, 2017). The amount of EDTA used in beans cooking has been variable and ranged from 0.5 g/L to 2 g/L, depending on the boiling time of beans (El-Naggar et al, 2019b). About 1.5 h were enough for V. faba beans to be well cooked in the presence of 2 g/L of EDTA, compared with 6 h in EDTA-free water.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To accelerate the cooking process and reduce the cost of cooking, some chefs use additives such as citric acid, sodium bicarbonate, and ethylenediaminetetraacetic acid (EDTA) (Lamas et al, 2014; Lanigan and Yamarik, 2002) where the latter was found to decrease the degree of starch gelatinization of black beans ( Phaseolus vulgaris L. ) (Mubaiwa et al, 2017). The amount of EDTA used in beans cooking has been variable and ranged from 0.5 g/L to 2 g/L, depending on the boiling time of beans (El-Naggar et al, 2019b). About 1.5 h were enough for V. faba beans to be well cooked in the presence of 2 g/L of EDTA, compared with 6 h in EDTA-free water.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, administration of EDTA orally produced reproductive and developmental adverse effects in animals (Khalil et al, 2008; Lanigan and Yamarik, 2002). According to our recent study, we have reported that adding EDTA to beans during cooking led to the formation of new compounds and ultimately diminishing the nutritional values of beans (El-Naggar et al, 2019b). Therefore, we hypothesized that the presence of EDTA in bean cooking media might be toxic upon administration into naïve mice for prolonged time.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that ethylene diamine tetra-acetic acid (EDTA) promotes the depletion of some metals and alters some cellular physiological functions on the living organisms [1,2]. It modifies the enterocytes permeability of cell membranes, which in turn enhances the rate of absorption of some biomolecules and drugs [3].…”
Section: Introductionmentioning
confidence: 99%
“…Only a small number of studies go beyond the general detectability and investigate for instance stability constants of Cu 2+ ‐, Zn 2+ ‐ and Ni 2+ ‐EDTA by ESI‐MS 22 . Barely any information is available on the fragmentation behavior of uncomplexed EDTA, 23,24 while no data on metal‐EDTA complexes are available.…”
Section: Introductionmentioning
confidence: 99%